PERBANDINGAN KEAKURATAN MODEL ARUS KAS METODE LANGSUNG DAN TIDAK LANGSUNG DALAM MEMPREDIKSI ARUS KAS DAN DIVIDEN MASA DEPAN - NORA UTARI (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2013)
Cash flow information of company is useful for users of financial reports as a basis for assessing a company’s ability to meet the needs of liquidity or cash flow. Cash flow information also enables users of financial statements to develop models to assess and compare the present value of future cash flows from various companies in one sector. Some previous researches on the prediction of future cash flows and dividend showed different results. This research should be repeated to examine the ability of cash flow in predicting future cash flows and dividend. The purpose of this research is to find the empirical evidence of predictive models of future cash flows and dividend. The samples of this study are manufacturing companies listed in Indonesia Stock Exchange (IDX). The amount of the samples are 24 companies within the period of 2009-2011. The data was collected using purposive sampling method. The result of this study shows that a combination of earnings and accrual is able to predict future cash flows so the indirect method is more accurate in predicting future cash flows. However, a combination of cash inflows and cash outflows using direct method is more accurate in predicting future dividend.